Endoplasmic Reticulum Stress Mediates Methamphetamine-Induced Blood–Brain Barrier Damage - Qie, Xiaojuan; Wen, Di; Guo, Hongyan; Xu, Guanjie; Liu, Shuai; Shen, Qianchao; Liu, Yi; Zhang, Wenfang; Cong, Bin; Ma, Chunling (Frontiers in Pharmacology, 2017)
Methamphetamine (METH) abuse causes serious health problems worldwide, and long-term use of METH disrupts the blood–brain barrier (BBB). Herein, we explored the potential mechanism of endoplasmic reticulum (ER) stress in METH-induced BBB endothelial cell damage in vitro and the therapeutic potential of endoplasmic reticulum stress inhibitors for METH-induced BBB disruption in C57BL/6J mice. Exposure of immortalized BMVEC (bEnd.3) cells to METH significantly decreased cell viability, induced apoptosis, and diminished the tightness of cell monolayers. METH activated ER stress sensor proteins, including PERK, ATF6, and IRE1, and upregulated the pro-apoptotic protein CHOP. The ER stress inhibitors significantly blocked the upregulation of CHOP. Knockdown of CHOP protected bEnd.3 cells from METH-induced cytotoxicity. Furthermore, METH elevated the production of reactive oxygen species (ROS) and induced the dysfunction of mitochondrial characterized by a Bcl2/Bax ratio decrease, mitochondrial membrane potential (MMP) collapse, and cytochrome c. ER stress release was partially reversed by ROS inhibition, and cytochrome c release was partially blocked by knockdown of CHOP. Finally, PBA significantly attenuated METH-induced sodium fluorescein (NaFluo) and Evans Blue leakage, as well as tight junction protein loss, in C57BL/6J mice. These data suggest that BBB endothelial cell damage was caused by METH-induced endoplasmic reticulum stress, which further induced mitochondrial dysfunction, and that PBA was an effective treatment for METH-induced BBB disruption.